2017
DOI: 10.22616/erdev2017.16.n087
|View full text |Cite
|
Sign up to set email alerts
|

Biogas potential from demaged bread

Abstract: Abstract. Latvian bakeries for various reasons result in production of waste and non-standard bread, which cannot be used for food. Damaged bread accumulates and stores mold. The bread utilization is problematic for manufacturers and traders. Environmental solution of this problem can be the usage of damaged bread for biogas production. This article shows the results of investigated biogas potential from five different damaged breads. Sixteen 0.75 liter bioreactors were filled with inoculums or with inoculums … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 4 publications
0
7
0
Order By: Relevance
“…Our previous study with damaged bread has shown that the specific biogas volumes (methane percentage in biogas) obtained after 30 days of the anaerobic digestion (AD) process were the following: 'French bread' 0.723 l•g -1 DOM (50.6 %); 'Rye flour bread' 0.634 l•g -1 DOM (49.9 %); 'Wheat flour (coarse) bread' 0.731 l•g -1 DOM (50.9 %); 'Toaster bread' 0.694 l•g -1 DOM (44.9 %), and 'White bread' (with egg and milk additives) 0.943 l•g -1 DOM (45.4 %) [5]. The results show that damaged bread can be used for biogas production successfully.…”
Section: Introductionmentioning
confidence: 99%
“…Our previous study with damaged bread has shown that the specific biogas volumes (methane percentage in biogas) obtained after 30 days of the anaerobic digestion (AD) process were the following: 'French bread' 0.723 l•g -1 DOM (50.6 %); 'Rye flour bread' 0.634 l•g -1 DOM (49.9 %); 'Wheat flour (coarse) bread' 0.731 l•g -1 DOM (50.9 %); 'Toaster bread' 0.694 l•g -1 DOM (44.9 %), and 'White bread' (with egg and milk additives) 0.943 l•g -1 DOM (45.4 %) [5]. The results show that damaged bread can be used for biogas production successfully.…”
Section: Introductionmentioning
confidence: 99%
“…The temperature for digestion of these wastes was Biogas, methane, bakery waste, Modern Civilization is based on high energy consumption. On an average, each citizen living on the earth consumes 2 t of carbon in a year for energy needs [1].Looking on to these problems of energy crisis solid waste must be processed for energy Solid waste generated during bakery materials production if treated by anaerobic digestion provides good results. Anaerobic digestion is a degradation of organic substances by microorganisms in the absence of oxygen.…”
Section: Introductionmentioning
confidence: 99%
“…2020. 16 (4) for biogas and high-quality fertilizers. however, the biogas release during the fermentation of manure is relatively low due to a sufficiently large amount of crude fiber.…”
mentioning
confidence: 99%
“…Analysis of recent research and publications on the grain waste disposal show that their anaerobic processing is the most effective for biogas production. According to the results of the study described in research [3], the re lease of biogas at a fermentation temperature of 38°с from substrates with the addition of rye bread is 0.459 l/g dry organic matter (DoM), in research [4], various types of grain release -from 0.634 l/g DoM (for rye bread) to 0.943 l/g DoM (for wheat bread with egg and milk additives). As it is stated in research [5], the common fermentation of biowaste with the waste of wheat and rye bread with an organic loading ra te of 14 kg/m 3 per day, was stable to their organic loading rate kg/m 3 per day and enabled producing 3 times mo re biogas.…”
mentioning
confidence: 99%
See 1 more Smart Citation